Private Sector Deleveraging and Growth Following Busts - Chen, Sally (IMF Working Papers; Working Paper ;, 2015)
Balance sheet recessions have been a drag on activity after the Global Financial Crisis, underscoring the important role of balance sheet adjustment for resuming sustained growth. In this paper we examine private sector deleveraging experiences across 36 advanced and emerging economies countries since 1960. We consider the common features and divergent experiences of deleveraging episodes across countries, and analyze empirically the impact of different aspects of deleveraging during the bust phase of leverage cycles on subsequent medium-term growth. The results suggest that larger and quicker unwinding of non-financial sector debt overhangs is associated with sizable medium-term output gains, and that policies should focus on facilitating up-front balance sheet adjustment.